EE Tech News Edition 2 2019/ Faculty of Electrical Engineering UiTM Terengganu - UiTM Terengganu, Faculty of Electrical Engineering (Faculty of Electrical Engineering, 2019)
Includes articles and activities held by Faculty of Electrical Engineering's students and staffs at UiTM Terengganu Dungun Campus.